Interleukin-22 promotes proliferation of liver stem/progenitor cells in mice and patients with chronic hepatitis B virus infection - Feng, Dechun; Dooley, Steven; Weng, Honglei (Gastroenterology, 2012)
Background & Aims: Proliferation of liver stem/progenitor cells (LPCs), which can differentiate into hepatocytes or biliary epithelial cells, is often observed in chronically inflamed regions of liver in patients. We investigated how inflammation might promote proliferation of LPCs. Methods: We examined the role of interleukin (IL)-22, a survival factor for hepatocytes, on proliferation of LPCs in patients with chronic hepatitis B virus (HBV) infection and in mice. Proliferation of LPCs in mice was induced by feeding a diet that contained 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC). Results: Hepatic expression of IL-22 was increased in patients with HBV and correlated with the grade of inflammation and proliferation of LPCs. Mice on the DDC diet that overexpressed an IL-22 transgene specifically in liver (IL-22TG), or that were infected with an IL-22-expressing adenovirus, had increased proliferation of LPCs. Signal transducer and activator of transcription (STAT) 3, a component of the IL-22 signaling pathway, was activated in LPCs isolated from DDC-fed IL-22TG mice. Deletion of STAT3 from livers of IL-22TG mice reduced proliferation of LPCs. In addition, the receptors IL-22R1 and IL-10R2 were detected on epithelial cell adhesion molecule+CD45− LPCs isolated from DDC-fed wild-type mice. Culture of these cells with IL-22 activated STAT3 and led to cell proliferation, but IL-22 had no effect on proliferation of STAT3-deficient EpCAM+CD45− LPCs. IL-22 also activated STAT3 and promoted proliferation of cultured BMOL cells (a mouse LPC line). Conclusions: In livers of mice and patients with chronic HBV infection, inflammatory cells produce IL-22, which promotes proliferation of LPCs via STAT3. These findings link inflammation with proliferation of LPCs in patients with HBV infection.